Women Writing Portuguese Colonialism in Africa (Volume 22) - Ferreira, Ana Paula (Liverpool University Press, 2020)
This book represents the first attempt to query the contribution of women as cultural agents to the colonization, the anti-colonial opposition and the decolonization of territories ruled by Portugal in the African continent between the turn of the twentieth century and the early twenty-first. In contrast to the longstanding scholarship on the subject as regards other European empires, the entanglement of gender and colonialism has been ignored in the Portuguese case. Hence, this book takes a long view, surveying mostly little known historical and literary records that evince how "women" and "colonialism" were discursively constructed at particular points in time in view of a colonialist project that became the reason for being of the fascist authoritarian regime (1933-1974). A cultural studies approach of radical contextualization informs each of the five main chapters, in which documents from a range of disciplines are brought to bear on the main problematic of the female-authored works in focus. The latter are all written in the metropole as a place of colonial return and critical reflection. Beyond recuperating women's voices, this book suggests a story of Portuguese colonialism in the African continent that is anything but Lusotropicalist.